2010
DOI: 10.1371/journal.pone.0013764
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Induces C/EBP-β-Mediated Activation of miR-31 in Normal Human Respiratory Epithelia and Lung Cancer Cells

Abstract: BackgroundLimited information is available regarding mechanisms by which miRNAs contribute to pulmonary carcinogenesis. The present study was undertaken to examine expression and function of miRNAs induced by cigarette smoke condensate (CSC) in normal human respiratory epithelia and lung cancer cells.MethodologyMicro-array and quantitative RT-PCR (qRT-PCR) techniques were used to assess miRNA and host gene expression in cultured cells, and surgical specimens. Software-guided analysis, RNA cross-link immunoprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 59 publications
4
100
1
Order By: Relevance
“…20 proliferation and tumourigenicity of lung cancer cells while knock-down of miR-31 inhibits growth of these cells [154]. Collectively, these data suggest that miR-31 activates Wnt signalling in cultured lung cancer and normal respiratory epithelial cells [155].…”
Section: Accepted M Manuscriptmentioning
confidence: 85%
“…20 proliferation and tumourigenicity of lung cancer cells while knock-down of miR-31 inhibits growth of these cells [154]. Collectively, these data suggest that miR-31 activates Wnt signalling in cultured lung cancer and normal respiratory epithelial cells [155].…”
Section: Accepted M Manuscriptmentioning
confidence: 85%
“…These data and previous reports from other groups link MIR31HG to cancer. In lung and breast cancers MIR31HG was shown to be upregulated 50,51 , whereas in triplenegative breast cancer it appears to be downregulated due to promoter hypermethylation 34 . The mechanism for MIR31HG upregulation in breast and lung cancer remains unknown.…”
Section: E1mentioning
confidence: 96%
“…MIR31HG has been previously reported to be deregulated in human cancers 34,50,51 . In our model system, MIR31HG is driven by B-RAF oncogene activation.…”
Section: Mir31hg Is Induced During Oismentioning
confidence: 98%
“…One of them, mir-218, is also down regulated in several cancers, and the authors revealed that modulation of miR-218 levels lead to changes in the expression of its target genes. Xi et al (2010) found that cigarette smoke condensate causes a significant and early increase in miR-31 that was apparent within 24 hours after exposure and persisted for 20 days after removal of the exposure.…”
Section: Epigenetics and Environment Exposurementioning
confidence: 96%